Comparison of Effects of Acellular Dermal Matrix and Latissimus Dorsi Muscle Flap on Radiation-induced Peri-implant Capsular Contracture in a Rabbit Model - Jang, Suk Yoon; Ahn, Il Young; Bae, Tae Hui; Kang, Shin Hyuk; Woo, Soo Hyun; Kim, Woo Ju; Kim, Mi Kyung; Sutthiwanjampa, Chanutchamon; Kim, Han Koo (Archives of Plastic Surgery, 2024)
Background Capsular contracture of breast implants is a major complication in breast surgery. Clinically, covering a breast implant with acellular dermal matrix (ADM) or autologous tissue is considered to be the most effective technique to prevent capsular contracture. This study was designed to compare the protective effects of ADM and latissimus dorsi (LD) muscle flap placement on capsular contracture by increasing the rate of capsular contracture through controlled radiation exposure in a rabbit model.Methods Twenty New Zealand white rabbits were divided into three groups. After the implant was placed beneath the pectoralis major muscle, the lateral third of the implant was left exposed in the control group (n = 6). In the ADM group (n = 7), the exposed implant was covered with AlloDerm. In the LD flap group (n = 7), the exposed implant was covered with a pedicled LD muscle flap. All groups were irradiated 3 weeks after implant insertion. After 6 months, peri-implant tissues were harvested and analyzed.Results ADM showed markedly lower myofibroblast activity than the LD flap. However, transforming growth factor-β1 levels and the activity of collagen types I and III produced in fibroblasts were significantly lower in the ADM group than in the LD flap group.Conclusion Based on the findings of our rabbit experiments, ADM is expected to have a comparative advantage in reducing the risk of capsular contracture compared to the LD flap.
Keywords: silicone breast implant; acellular dermal matrix; latissimus dorsi muscle flap; radiation-induced capsular contracture